2013
DOI: 10.1001/jamaophthalmol.2013.4056
|View full text |Cite
|
Sign up to set email alerts
|

Paracentral Acute Middle Maculopathy

Abstract: IMPORTANCE With the advent of more sophisticated imaging systems, such as spectral domain optical coherence tomography (SD-OCT), disruption of the inner segment/outer segment (IS/OS) band, and thinning of the outer nuclear layer (ONL) have been identified in association with acute macular neuroretinopathy (AMN). OBJECTIVES To characterize a new SD-OCT presentation of AMN as a paracentral acute middle maculopathy and to describe multimodal imaging findings that implicate an underlying pathogenesis related to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
232
0
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 393 publications
(244 citation statements)
references
References 30 publications
7
232
0
5
Order By: Relevance
“…34 PAMM lesions were originally proposed to be the result of ischemia of the SCP, 34 but consideration of the anatomical location of the MCP immediately superficial to PAMM lesions suggests more likely involvement of this plexus. 35 Further emphasizing the importance of improved segmentation of MCP, recent case studies of PAMM imaged using OCTA have demonstrated attenuated blood flow of the DCP.…”
Section: Discussionmentioning
confidence: 99%
“…34 PAMM lesions were originally proposed to be the result of ischemia of the SCP, 34 but consideration of the anatomical location of the MCP immediately superficial to PAMM lesions suggests more likely involvement of this plexus. 35 Further emphasizing the importance of improved segmentation of MCP, recent case studies of PAMM imaged using OCTA have demonstrated attenuated blood flow of the DCP.…”
Section: Discussionmentioning
confidence: 99%
“…5 This case appears unique as a type 1 PAMM lesion, as prior cases were mostly seen in older males. 1 Previously described AMN/PAMM cases were related to hypertensive- or vasoconstrictive-inducing substances. In this case, the combined hypotension/anemia as well as hypercoagulable state of pregnancy may have contributed to the ischemic event.…”
Section: Discussionmentioning
confidence: 99%
“…AMN has been associated with vasoconstrictors and sympathomimetics. 1 In 2013, paracentral acute middle maculopathy (PAMM) was described as an AMN variant, seen as a hyperreflective band involving the middle retinal layers on spectral-domain optical coherence tomography (SD-OCT). 1 Type 1 PAMM lesions involve layers above the outer plexiform layer (OPL), reflecting superficial or intermediate capillary plexus occlusion; type 2 lesions involve layers below the OPL, affecting the deep capillary plexus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…46 The PAMM lesions, associated with retinal vascular disease, may resolve and lead to retinal thinning and paracentral scotomas. 6 …”
Section: Discussionmentioning
confidence: 99%